"Escrevo numa língua que não é minha.": apontamentos sobre processo de ensino e aprendizagem da língua portuguesa escrita por surdos alfabetizados - Sant'Anna, Telma Gomes Novato (2012)
In an educational context of Strong worldwide movement in favor of inclusive education, which proposes to accommodate all students regardless of their beliefs, race, socio;economic status, or the ones who have physical, sensory, or intellectual disabilities, this research aims to investigate, discuss (and glimpse) paths to the acquisition of written Portuguese by deaf students. For this purpose, the analyzed data were collected in a public school, especially in the Portuguese language classes at Atendimento Educacional Especializado (AEE; Specialized Educational Services). The select subjects were two deaf teenage girls, who, in the academic year of 2011, were regularly enrolled in the first year of high school and attended, twice a week, the AEE. After introducing a brief history and legal aids of the education of deaf students, this study discusses, articulating the bilingual proposal, in which Portuguese is a second language, and the operation of this language and speech as constitutive activity of the individual, the practices of writing texts by deaf students in their social and academic spheres. The data analyzes shows that the mediation is the crux of the whole process. It is through mediation, that is to say, in a joint activity with an adult user of both languages, that the deaf student is captured by the written language to make is work as a resource for interaction and dialogue according to what to say, the reason to say, to whom say and constitute himself as an individual who says what he says to whom he says. (Geraldi, 2003, p.137)